Detoxification Mechanism of 8,8-Dimethyl-3-[(R-Phenyl)Amino]-1,4,5(8h) -Naphthalentrione Derivatives by Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The effect of 8,8-dimethyl-3-[(R-phenyl)amino]-1,4,5(8H)-naphthalentrione derivatives (compounds 1–13) on the mycelial growth of Botrytis cinerea was evaluated. The fungitoxic effect depended on the substituent and its position in the aromatic ring. Compounds substituted with halogens in meta and/or para positions (compounds 3, 4, 5 and 7), methyl (compounds 8 and 9), methoxyl (compounds 10 and 11), or ethoxy-carbonyl groups (compound 12) presented higher antifungal activity than compound 1, which had an unsubstituted aromatic ring. In addition, compounds with halogens in the ortho position, such as compounds 2 and 6, and a substitution with an acetyl group in the para position (compound 13) were less active. The role of the ABC efflux pump Bctr B-type as a defense mechanism of B. cinerea against these naphthalentrione derivatives was analyzed. This pump could be involved in the detoxification of compounds 2, 6, and 13. On the contrary, this mechanism would not participate in the detoxification of compounds 1, 7, 9 and 12. Finally, the biotransformation of compound 7 by B. cinerea was studied. A mixture of two biotransformed products was obtained. One of them was compound 7A, which is reduced at C1 and C4, compared to compound 7. The other product of biotransformation, 7B, is oxidized at C7. © 2019 by the authors.